OPEN ONLINE COURSES AS A TOOL FOR MODERNIZATION OF EDUCATIONAL PROCESS IN UNIVERSITIES - Vastly S. Tretyakov; Viola A. Larionova (Moscow Polytechnic University, 2016)
The article reveals a potential of open online courses in higher education in order to increase its efficiency and availability. The organizational and methodological aspects of e-learning development in higher education are considered. The economic background for implementing open online courses in the educational process is under analysis. On the basis of benchmarking the best foreign and Russian practices the authors propose different cases for online courses implementation to higher education programs, as well as organizational and financial schemes of interaction between higher education institutions.